Effect of The Proportion Of Wheat Flour: Fermented Jali Flour And Additional NahCo3 on Physical, Chemical and Organoleptic Characteristics of Crackers - Intan Tri Oktarini; Rosida Rosida; Luqman Agung W (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Jali flour can be used as a substitute for flour in crackers to reduce the use of wheat in Indonesia. The purpose of this study was to determine the effect of the proportions of wheat flour: fermented jali flour and the addition of NaHCO3 on the properties of crackers and to obtain the best treatment based on physical, chemical and organoleptic properties. The design of this study was a completely randomized design (CRD) with two factors, namely the proportion of wheat flour: fermented jali flour (70:30; 60:40; 50:50) and the addition of NaHCO3 (0.25; 0.5; 0.75) %. The best treatment with the proportion ratio of wheat flour: fermented jali flour 70:30 with the addition of 0.75% NaHCO3, 4.71% moisture content, 1.94% ash content, 7.45% protein content, 6.84% fat content, carbohydrates 79.06%, amylose content 6.35%, expansion 69.98%, crispness 254.33%, taste score 3.8 (like), texture 3.6 (like), taste 3.6 (like) and color 3.7 (like).